2011
DOI: 10.1074/jbc.m111.247411
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Serine Acetyltransferase Is Involved in Nickel Hyperaccumulation in Thlaspi goesingense

Abstract: When growing in its native habitat, Thlaspi goesingense can hyperaccumulate 1.2% of its shoot dry weight as nickel. We reported previously that both constitutively elevated activity of serine acetyltransferase (SAT) and concentration of glutathione (GSH) are involved in the ability of T. goesingense to tolerate nickel. A feature of SAT is its feedback inhibition by l-cysteine. To understand the role of this regulation of SAT by Cys on GSH-mediated nickel tolerance in T. goesingense, we characterized the enzyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 43 publications
0
9
1
Order By: Relevance
“…Both species were grown from seeds collected from plants growing on contaminated sites where S input from industry (Jena) and smelting activities (Vogel-Mikus et al, 2005) probably was high. Unexpected, and in contrast to our working hypothesis, was the finding that N. caerulescens had the lowest GSH concentrations among the species  2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim www.plant-soil.com (Na and Salt, 2011a). This distinctive pattern was not followed by the species in this study with high GSH concentrations in T. arvense (nonhyperaccumulator) and N. praecox (hyperaccumulator) and lower concentrations in N. caerulescens (hyperaccumulator).…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Both species were grown from seeds collected from plants growing on contaminated sites where S input from industry (Jena) and smelting activities (Vogel-Mikus et al, 2005) probably was high. Unexpected, and in contrast to our working hypothesis, was the finding that N. caerulescens had the lowest GSH concentrations among the species  2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim www.plant-soil.com (Na and Salt, 2011a). This distinctive pattern was not followed by the species in this study with high GSH concentrations in T. arvense (nonhyperaccumulator) and N. praecox (hyperaccumulator) and lower concentrations in N. caerulescens (hyperaccumulator).…”
Section: Discussioncontrasting
confidence: 82%
“…It was hypothesized that in this Ni hyperaccumulator SA inhibits PC formation and activates serine-acetyl transferase (SAT) leading to accumulation of GSH and activation of glutathione reductase, thus protecting plants from Ni-induced oxidative stress (Freeman et al, 2005). These SAT isoforms are insensitive to inhibition by cystein (Na and Salt, 2011a). However, the observation that the inhibition of c-glutamylcysteine synthetase by L-buthionine sulfoximine (BSO) does not decrease metal hypertolerance in N. caerulescens (Schat et al, 2002) has been used as an argument against a role for GSH and PCs in metal tolerance in this hyperaccumulator (Krämer, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In EhSAT3, the position equivalent to Met201 is already occupied by valine, which may account for its lack of sensitivity for cysteine inhibition. There are several studies indicating the importance of the C-terminal residues in Cys feedback inhibition [24], [25]. The Saito and his coworkers showed that Met to Ile mutation at the C-terminal 280 residue in the watermelon SAT decreased the Cys inhibition by 25 folds and Gly 277 Cys mutant also showed similar Cys inhibition [24].…”
Section: Discussionmentioning
confidence: 99%
“…In both EhSAT1 and EhSAT3, the equivalent residue of 280 is already Ile and 277 is Ile and Glu respectively (Figure S4), therefore we expect these residues may not play any role in Cys inhibition in Entamoeba SAT’s. By comparing A. thaliana and T. goesingense SAT sequences, GunNan and Salt [25] proposed that Pro and Ala at 268 and 270 th position of T. goesingense SAT might be responsible for Cys insensitivity. At these positions EhSAT1 has serine and glutanmine, while EhSAT3 has glutamine at both positions; moreover this C-terminal end region has very little sequence similarity between EhSAT’s and TgSAT (Figure S4).…”
Section: Discussionmentioning
confidence: 99%
“…Protein was quantified by Bradford method and NanoDrop ND-1000 (Thermo Scientific). Equal amounts of eluates were fractionated by SDS/PAGE and visualized by silver staining (Pierce) and Western blot by using a polyclonal anti-SAT antibody (44).…”
Section: Methodsmentioning
confidence: 99%